Evaluación del cumplimiento de la normativa legal relacionada al anticipo del impuesto a la renta - Morocho Caraguay, Karina Elizabeth (2015)
The work is directly related to the assessment of compliance of the advance payment of income tax by the taxpayer José Eduardo Morocho city of Machala, it keeps correspondence with an Office Automation model that will help improve processing the accounting information that is directly linked to the items to be taken for the calculation of the tax; As major papers have been highlighted TAX REGIME OF INDIVIDUALS AFTER THE 1607 ACT OF 2012 and scientific rigor in qualitative research. This proposal is directly aimed at improving the situation of the company, avoiding mistakes in its determination, and therefore eradicates the presence of taxes and fines. Further mention of Circular No. NAC-DGECCGC13-00007 issued by the Internal Revenue Service, as systematically be used by taxpayers who are required to declare the payment of income tax, by its operations or level of income is They encountered during the corresponding fiscal year. Its main objective is to contribute to the owner of the company, subject to study, has appropriate technique to optimize their resources. The qualitative methodology is the best choice for the development of this project, starting the collection of information obtained through the techniques employed. In conclusion we can say that the control of resources arising from the activities of the company must be consistent with the laws for this purpose so that we would recommend to carry out a rigorous and concurrent control of all resources available to the company, In order to achieve business growth in a safe and sustainable way, the best results with the least possible investment.